The Effect of Training, Work Motivation and Work Discipline on Employee Performance at PT Maya Gapura Intan Bandung - Wijaya, Nani; Sudarijati, Sudarijati; Samsuri, Samsuri (Westscience Press, 2024)
Employee performance is a result that a person achieves in carrying out the tasks and responsibilities given to him based on skills, experience and perseverance and time at work. Given the influence of training, work motivation provided by the company and work discipline carried out by employees, so that employee performance can increase in an effort to achieve company goals. This study aims to determine the effect of training, work motivation and work discipline on employee performance. The analysis method used in this research is multiple linear regression analysis with a quantitative approach. The total sample size was 43 people. The results in this study indicate that training, work motivation and work discipline simultaneously have a positive and significant effect on employee performance, while partially each variable of training, work motivation and work discipline has a positive and significant effect on employee performance.